Study of Four Rainstorm Design Methods in Chongqing - Liao, Daiqiang; Zhang, Qiang; Wang, Ying; Zhu, Haonan; Sun, Jia (Frontiers in Environmental Science, 2021)
Based on minute-by-minute precipitation data from 1961 to 2016 obtained from the National Basic Weather Station of Shapingba, Chongqing, China, the Chicago rainstorm method, the Pilgrim & Cordery (P&C) method, the Common-frequency method and the natural rainstorm moving regularity (NRMR) method were used to design short-duration (1-3 hours) and long-duration (24 hours) rainstorm hyetographs. Then, a standardization method for test samples was designed to ensure that each test sample was standardized and underwent an actual precipitation process. The designed rainstorm hyetographs and test samples were compared and analyzed, and the results show that the hyetographs for the 1-h, 3-h and 24-h durations obtained with the NRMR method best represented the actual corresponding precipitation processes. The hyetograph for the 2-h duration obtained with the Chicago rainstorm method was best for the actual 2-h precipitation process. The design results of the Common-frequency method were generally good, but not outstanding. Finally, the P&C method showed a relatively poor performance for each duration.